El costo en bienestar de una inflación perfectamente prevista - Ayala Salcedo, Roberto (2001)
This article presents an estimation of inflation costs for Ecuador and the benefits that would be obtained trom reducing inflation to one-digit levels. Estimates of real demand for money as well as short term and long term interest rato clastivitics aro calculated. With these results and using the methodology presented by Bailey (1956), the authors find the inflation costs function. For the case of Ecuador, these costs represent 4.85% of quarter GDP in the long rua, and 1.30% of quarter GDP in the short term. The estimated benefits from reducing inflation to one-digit levels are 3.24% of quarter GDP in the long term, and 0.98 % in the short run.